SISTEM REKOMENDASI PEMILIHAN PRODUK BASIC SKINCARE BERDASARKAN JENIS KULIT MENGGUNAKAN ALGORITMA SIMPLE ADDITIVE WEIGHTING (SAW) - Mina Ismu Rahayu; Mira Kasegrina Siregar; Melly Desnia (LPPM STMIK Bandung, 2022)
In general, women want to have clean and healthy skin so they feel more confident. To get healthy and cleanskin, of course you need to work hard to care for and choose skin care products that are suitable for yourfacial skin. Some sequences of using the right skin care products are serum, serum, moisturizer, sunscreen.Before knowing the right basic skin care products, we need to know about each of our skin types. In thiswebsite-based skin care recommendation system, we need to enter each standard type, and the system willprovide skin care recommendations. The method used is the Simple Additive Weighting (SAW) algorithmwith weight and ranking calculations, the results of this calculation will bring the largest value as a skincarerecommendation.